Density based hybrid recommender system combining demographic methods and collaborative filtering [electronic resource] - 512683 Siavash Ghodsi Moghaddam (2011)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2011